Essai sur la Monarchie autrichienne en son état actuel en 1790 - Derek Beales (Biblioteca di storia, 2018)
L'Essai sur la Monarchie autrichienne en son état actuel en 1790 offers a complete and unprecedented overview of the conditions of the Hapsburg monarchy on an international levell at the beginning of the French Revolution. This essay is addressed at a non-specialist reader, likely identified with future emperor Francis II's betrothed. It examines the institutional, economic, military and religious context of the monarchy, establishes its historical and political legitimacy and suggests a disenchanted evaluation of the emperor Joseph II's work shortly after his death. On the whole, it represents an exceptional testimony to the processes taking place in the heart of Europe in an era of dramatic changes.